(untitled) (Asian Journal of Medical and Biological Research, 2016)
A research work was undertaken to evaluate the feeding effect of tree forages on performance of growing sheep. Twenty growing sheep (in 4 groups) were fed three different tree forage diets. Tree forages Melia azardirachta, Leucaena leucocephala and Artocarpus heterophyllus were supplied in three treatments except one consisted no tree forages which was considered as control. There were significant (p<0.05) differences among the animal groups in terms of total DM and ME intake, although there were no significant differences in the digestibility of DM, OM, CP and ADF. Feeding of tree forages had significant (p<0.05) effect on live weight gain of sheep. Animals fed with tree forage based diets significantly increased weight gain (60.70 and 50.70 g/d for L. leucocephala and A. heterophyllus, respectively) compared to that (45.66 g/d) of control group fed with silage. Feed conversion efficiency (kg feed/kg gain) also showed that animals fed with tree forage of L. leucocephala and M. azardirachta based diets were having significantly (p<0.05) higher efficiency (11.33 and 11.47, respectively) compared to those of A. heterophyllus and control diet (13.77 and 13.33, respectively). The results of nitrogen balance of M. azardirachta and L. leucocephala tree forage had significantly (p<0.05) positive effect on the nitrogen retention in the body of the animals. Intake of all the tree forages was not similar which indicated that all of them were not accepted to the lamb in same level. So, diets with tree forages of L. leucocephala resulted better in terms of weight gain, digestibility and nitrogen balance compared to A. heterophyllu, M. azardirachta and silage (control). Asian J. Med. Biol. Res. December 2015, 1(3): 654-659